Back Cover: Conversion of Cellulose into Isosorbide over Bifunctional Ruthenium Nanoparticles Supported on Niobium Phosphate (ChemSusChem 11/2013). Issue 11 (25th October 2013) - Sun, Peng; Long, Xiangdong; He, Hao; Xia, Chungu; Li, Fuwei
<x xml:space="preserve">Abstract</x> The back cover image shows the production of isosorbide from the one‐pot hydrolytic hydrogenation and dehydration of inedible cellulose. Dr Fuwei Li and co‐workers show that isosorbide production can be achieved under hydrothermal conditions over a recyclable ruthenium catalyst supported on mesoporous niobium phosphate without the addition of soluble acids. This efficient and sustainable protocol could close the carbon cycle as a result of plants taking up CO2 generated from the end products. More details can be found in the Full Paper by Sun et. al on page 2190 (DOI: 10.1002/cssc.201300701).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>